Using a Delphi study to clarify the landscape and core outcomes in environmental education. Issue 3 (3rd March 2020) - Clark, C. R.; Heimlich, J. E.; Ardoin, N. M.; Braus, J.
Abstract: When leaders in a field agree upon core outcomes for the field, connection, reinforcement, and a shared vision of change are synergistically strengthened. Even when the field is dynamic, theoretically wide-ranging, and dispersed, consensus around core outcomes can help develop strategic research agendas and priorities. Environmental education (EE) is an inherently interdisciplinary field drawing on diverse theoretical foundations and epistemological orientations, resulting in a broad conceptual and empirical landscape. To better understand and situate this within EE, we pursued a modified Delphi study, with participation from 44 professionals and leaders active in North America. Over three Delphi rounds, the panel came to agreement on five core outcomes that focus the EE field: (1) environmentally related action and behavior change, (2) connecting people to nature, (3) improving environmental outcomes, (4) improving social/cultural outcomes, and (5) learning environmentally relevant skills and competencies. Reflecting those commonalities, we propose the following encapsulating statement to describe the field's core outcomes: Environmental education works to move people to action for the tangible benefit of the environment and humanity. To realize these benefits, people must connect experientially with the environment, learn needed skills, and understand the complicated social and cultural connections between humanity and the natural environment. Graphical Abstract: